Pupil participation in the construction of evaluation devices - Manley, Helen M., author; Morgan, David H., advisor; Williamson, Maude, committee member; Elliff, Rowan E., committee member; Holman, Mary V., committee member (Colorado State University. Libraries, 1943)
To view the abstract, please see the full text of the document.
Keywords: Clothing and dress -- Study and teaching